2019
DOI: 10.1093/scipol/scz028
|View full text |Cite
|
Sign up to set email alerts
|

Spaces of novelty: Can universities play a catalytic role in less developed regions?

Abstract: Over the past few decades, universities have been asked to become ever more involved in the development of their regions and countries, through knowledge dissemination, contribution to policy debates or even by becoming leaders in stakeholder coalitions. However, as has been often pointed out, for universities to have an impact on regional fortunes it is necessary to have an appropriate innovation ecosystem, which is often lacking in less developed regions. We approach this issue by discussing the three interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
0
20
0
2
Order By: Relevance
“…The literature on universities' roles has emphasised the combination and intersection of several models of engagement, which can give rise to "contradictions or conflicts of policy rationales and objectives" (Uyarra, 2010(Uyarra, : 1229. With studies pending towards private sector links and the more economic aspect of universities' regional engagement, this may lead to a skewed perception in the identification and conceptualisation of university roles, limiting awareness of universities' regional impact (Marques et al, 2019). Concomitantly, while universities are increasingly expected to participate in regional strategies, they are not homogenous institutions that can be predicted to contribute evenly.…”
Section: Towards a More Comprehensive Analysis Of Universities' Roles -Building A Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on universities' roles has emphasised the combination and intersection of several models of engagement, which can give rise to "contradictions or conflicts of policy rationales and objectives" (Uyarra, 2010(Uyarra, : 1229. With studies pending towards private sector links and the more economic aspect of universities' regional engagement, this may lead to a skewed perception in the identification and conceptualisation of university roles, limiting awareness of universities' regional impact (Marques et al, 2019). Concomitantly, while universities are increasingly expected to participate in regional strategies, they are not homogenous institutions that can be predicted to contribute evenly.…”
Section: Towards a More Comprehensive Analysis Of Universities' Roles -Building A Conceptual Modelmentioning
confidence: 99%
“…The increasing expectations placed upon universities, not only regarding knowledge dissemination, production and commercialisation, but also regional governance and strategy design, demonstrate a need for more comprehensive assessments and understanding of universities’ roles. Limiting universities’ regional roles to university–industry interactions and entrepreneurial or economic impact (Fonseca, 2019a; Pugh et al, 2016) works against the potential of universities to perform developmental roles and contribute knowledge as well as experience to regional development processes and strategies (Marques et al, 2019). There is still a lack of clarification on the exact roles universities are performing, and a tendency to conflate and homogenise these roles across institutions, contexts and timeframes (Flanagan et al, 2010; Uyarra, 2010), particularly in university–regional government relations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, some domains of analytical knowledge can themselves be commercialized to form the basis for new indigenous paths in science or technology-based fields (e.g., biotechnology, information and communication technology -ICT) that are only weakly related to established industries in the region (Isaksen & Trippl, 2017;Martin & Sunley, 2006;Vallance, 2016). Previous research has, however, demonstrated that these forms of analytical knowledge that originate from universities or public research organizations only translate into significant regional development outcomes when enabled by a wider innovation/entrepreneurial ecosystem of favourable institutional and market conditions (Marques et al, 2019). For highly novel technologies, these enabling conditions will not already be present in many regional contexts and will need to co-emerge with the entry of new firm actors (e.g., new start-up enterprises, external investors).…”
Section: Theoretical Background and Analytical Frameworkmentioning
confidence: 99%
“…Coal as a major source of regional wealth was not replaced and there is limited industrial diversification in the region (Morgan, 2017). Following this downturn, the economy has become characterized by a high degree of services activity (Henderson & Roche, 2020;Marques et al, 2019). Wales underperforms in relation to the UK average and has the highest level of Structural Funding from Europe (Pugh, 2017).…”
Section: Case Study Regionmentioning
confidence: 99%